Determinants of contraceptive use among postpartum women in a county hospital in rural KENYA - Rose Jalang'o; Faith Thuita; Sammy O. Barasa; Peter Njoroge (BMC, 2017)
Abstract Background There is a high unmet need for limiting and spacing child births during the postpartum period. Given the consequences of closely spaced births, and the benefits of longer pregnancy intervals, targeted activities are needed to reach this population of postpartum women. Our objective was to establish the determinants of contraceptive uptake among postpartum women in a county referral hospital in rural Kenya. Methods Sample was taken based on a mixed method approach that included both quantitative and qualitative methods of data collection. Postpartum women who had brought their children for the second dose of measles vaccine between 18 and 24 months were sampled Participants were interviewed using structured questionnaires, data was collected about their socio-demographic characteristics, fertility, knowledge, use, and access to contraceptives. Chi square tests were used to determine the relationship between uptake of postpartum family planning and: socio demographic characteristics, contraceptive knowledge, use access and fertility. Qualitative data collection included focus group discussions (FDGs) with mothers and in-depth interviews with service providers Information was obtained from mothers' regarding their perceptions on family planning methods, use, availability, access and barriers to uptake and key informants' views on family planning counseling practices and barriers to uptake of family planning Results More than three quarters (86.3%) of women used contraceptives within 1 year of delivery, with government facilities being the most common source. There was a significant association (p ≤ 0.05) between uptake of postpartum family planning and lower age, being married, higher education level, being employed and getting contraceptives at a health facility. One third of women expressing no intention of having additional children were not on contraceptives. In focus group discussions women perceived that the quality of services offered at the public facilities was relatively good because they felt that they were adequately counseled, as opposed to local chemist shops where they perceived the staff was not experienced. Conclusion Contraceptive uptake was high among postpartum women, who desired to procure contraceptives at health facilities. However, there was unmet need for contraceptives among women who desired no more children. Government health facility stock outs represent a missed opportunity to get family planning methods, especially long acting reversible contraceptives, to postpartum women.